Application of Information Technology in Human Resource Adit to Employee Performance in CV Prima Rasa Selarasa - Handayani, Nur Syfa Awaliyah; Yulianasari, Nina; Riswandi, Pedi (Ikatan Da'i Indonesia, 2024)
The purpose of this research is to analyze how the Application of Information Technology in Human Resources Audits on Employee Performance at CV. Prima Rasa Harmony. The results of this research show that in improving employee performance at CV Prima Rasa Selaras, the use of the Moka and Accurate Lite applications really helps the work, making it easier to process transactions carried out at each outlet without having to do it manually and taking a long time and in the process of using the Moka good application and Accurate Lite, there are still several weaknesses in the application, for example, not being able to refund, not being able to cancel orders and often experiencing response delays which result in the transaction process being slightly disrupted.